Design, Synthesis, and Preliminary Cardioprotective Effect Evaluation of Danshensu Derivatives. (1st July 2014) - Cui, Qingbin; Chen, Yonghong; Zhang, Mingjuan; Shan, Luchen; Sun, Yewei; Yu, Pei; Zhang, Gaoxiao; Wang, Dingyuan; Zhao, Zengchao; Xu, Qian; Xu, Benhong; Wang, Yuqiang
<x xml:space="preserve">Abstract</x> A series of (R)‐3, 4‐dihydroxyphenyllactic acid Danshensu (DSS) derivatives were synthesized, and their cardioprotective effects were evaluated in vitro and in vivo. Among the new derivatives, compound 14 showed significant protective effects in cultured myocardial cells and in the rat model of myocardial ischemia. The therapeutic efficacy of compound 14 was significantly higher than that of its parent compound DSS, and amlodipine, a first‐line treatment for angina pain. Compound 14 potently scavenged free radicals, significantly decreased the levels of LDH and MDA, and inhibited the leakage of CK in animal model of ischemia. We had previously found that compound 14 activated PI3K/Akt/GSK‐3β and Nrf2//Keap1/heme oxygenase‐1 (HO‐1) signaling pathways in H9c2 cells. These results suggest that compound 14 has a unique mechanism of action, that is, multifunctional. Compound 14 may be a new potential therapy for ischemic heart diseases.